The role of brain acetylcholine in GABAA receptor antagonist-induced blood-pressure changes in rat - (:unkn) unknown (My University, 1996)
Previous experimental studies have shown that intracerebroventricular (i.c.v.) injection of the GABAA receptor antagonist, bicuculline methiodide, results in marked increases in blood pressure due to an increase in sympathetic nervous system activity. It is well recognized that the central cholinergic system is also involved in the regulation of blood pressure. In the present study, we examined the role of brain acetylcholine in the pressor response induced by bicuculline methiodide in conscious Sprague-Dawley rats. I.c.v. (0.05, 0.3 and 0.5 nmol) and intrahypothalamic (40 pmol) administration of bicuculline methiodide produced blood-pressure increases in a dose-dependent manner. Hemicholinium-3 was given i.c.v. 1 h prior to bicuculline methiodide. The depletion of brain acetylcholine was demonstrated by the suppression of physostigmine-induced pressor responses, but blood pressure increases in response to carbachol remained unchanged. The pressor responses to bicuculline methiodide in animals pre-treated with hemicholinium-3 were significantly higher than those seen in saline-pre-treated groups. Likewise, bicuculline methiodide, at a dose that did not alter blood pressure alone, caused pressor responses in rats pre-treated with the nicotinic receptor antagonist, mecamylamine, whereas the muscarinic receptor antagonist, atropine, was ineffective in this respect. In conclusion, it seems likely that endogenous brain acetylcholine has a modulator role on GABAA receptor-mediated blood-pressure control via nicotinic receptors.
Keywords: Female; Animals; Rats; Blood Pressure; Rats, Sprague-Dawley; Injections, Intraventricular; Acetylcholine; Hypothalamus; Bicuculline; GABA Antagonists; Brain Chemistry; Carbachol; Cholinergic Agents; Cholinergic Agonists; Cholinesterase Inhibitors; GABA-A Receptor Antagonists; Hemicholinium 3; Physostigmine